The footwear industry of Vale do Sinos (RS) in the scope of Mercosur: challenges and potentialities - Rodrigues, Hildete Flores; Salomão, Ivan Colangelo (Faculdade de Ciências e Letras - Unesp - Araraquara., 2019)
This paper presents and analyzes the participation of the footwear sector of Sinos river Valley (RS) in the Mercosur, trying to identify its characteristics, challenges, and potentialities of the sector. With an important presence on the Brazilian export agenda, the footwear production chain has a significant impact on the local and national economies, and has been being modernized to face the challenges of internationalization that the growing Chinese presence represents for the Mercosur countries.